Effective Sentence Assignment as the Key to Improve Skill of Writing Exposition with Online Learning Media Quipper - Saddhono, Kundharu; Oktaria, Dinari; Muflikh Raharjo, Yusuf; Adi Nugroho, Rudi; ., Sudaryanto; Qomariyah, Uâ€™um; Vidya Asteria, Prima; Faizah, Umi (International Journal of Engineering and Technology, 2018)
This study aimed to determine the relationship between the mastery of effective sentences, activity of writing and writing skills exposition text using online learning media Quipper. This research was conducted in Vocational School Education of Surakarta. The method used is correlational survey method. The study population was all students in grade X Vocational School Education of Surakarta. Samples numbered 120 people were taken by proportional random sampling. Instruments for collecting data is a test of skill to write text exposition, effective sentences mastery tests, and questionnaires liveliness writing. The analysis technique used was the statistical technique of regression and correlation The analysis showed there is a positive correlation between mastery of effective sentences and liveliness writing together with the skills to write text exposition (Ry12 = 0.59 in the real level of Î±=0.05 with N=120, Rt=0.120,and F0=31 70ËƒFt=3.0764). Based on the research results obtained concluded that jointly effective sentence mastery and liveliness write a significant contribution (34.81%) in the text writing skills exposition. It shows that these two variables can be a good predictor for text writing skills exposition.Â Â